Pengaruh Kecerdasan Emosional, Kecerdasan Sosial dan Kecerdasan Intelektual terhadap Pemahaman Akuntansi: Survei pada Mahasiswa Program Studi Akuntansi STIEM Bongaya Makassar - Yusriadi Hala; Neng Indriyani; Rostiaty Yunus; Rezky Auliah (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The aim of this research is to find out whether emotional intelligence, social intelligence and intellectual intelligence partially affect the understanding of accounting in students of the accounting study program at STIEM Bongaya Makassar. The data collection technique uses primary data obtained through a questionnaire using a purposive sampling technique. The population is all students of the STIEM Bongaya Makassar accounting study program, totaling 273 people, while the sample taken is 85 students. The results of the questionnaire have been tested for validity and reliability, and classical assumptions have been tested in the form of normality assumption tests, multicollinearity tests and heteroscedasticity tests. Methods of data analysis using multiple linear regression techniques. The results of the study show that first, emotional intelligence does not have a positive and significant effect on understanding accounting. Second, social intelligence has a positive but not significant effect on accounting understanding, third, intellectual intelligence has a positive but not significant effect on accounting understanding